2016
DOI: 10.1259/bjr.20160298
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the sacroiliac joint vacuum phenomenon in paediatric patients

Abstract: Objective: To assess the incidence of the sacroiliac joint vacuum phenomenon (SIJ VP) in paediatric patients and the relationship between the presence of VP and clinical factors such as age, sex and body mass index (BMI). Methods: We retrospectively reviewed clinical data and imaging findings of 60 patients who underwent abdominopelvic CT (AP CT) between January and June 2015. Patients were divided into VP group and non-VP group based on the presence/absence of VP, and the groups were compared. In addition, ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…Although the presence of a vacuum phenomenon did not affect the lumbopelvic parameters in females, there was a significant decrease in pelvic incidence and sacral slope in males with a vacuum phenomenon [15]. A study by You et al concluded that prevalence of vacuum phenomenon in sacroiliac joint in children is the same as that of adults; however, they were not able to determine the association between degenerative changes in the sacroiliac joint and low back pain among children and adolescents [16] In acute open injury, the presence of air indicates communication of joint space to outside, even as an iatrogenic cause as in arthroscopy complicated by tension pneumoarthrosis [2]. The presence of intra-articular air may simulate meniscal and cartilaginous injury in the knee, but Miller et al and Wright et al showed the presence of air was actually associated with meniscal and bony injuries, respectively, in their patients` [12,17].…”
Section: Figure 1: Chest Radiograph Of a Three-year Infant Showing Pneumoarthrosis In Shoulder Joints Figure 2: Follow-up Radiograph Showmentioning
confidence: 94%
“…Although the presence of a vacuum phenomenon did not affect the lumbopelvic parameters in females, there was a significant decrease in pelvic incidence and sacral slope in males with a vacuum phenomenon [15]. A study by You et al concluded that prevalence of vacuum phenomenon in sacroiliac joint in children is the same as that of adults; however, they were not able to determine the association between degenerative changes in the sacroiliac joint and low back pain among children and adolescents [16] In acute open injury, the presence of air indicates communication of joint space to outside, even as an iatrogenic cause as in arthroscopy complicated by tension pneumoarthrosis [2]. The presence of intra-articular air may simulate meniscal and cartilaginous injury in the knee, but Miller et al and Wright et al showed the presence of air was actually associated with meniscal and bony injuries, respectively, in their patients` [12,17].…”
Section: Figure 1: Chest Radiograph Of a Three-year Infant Showing Pneumoarthrosis In Shoulder Joints Figure 2: Follow-up Radiograph Showmentioning
confidence: 94%
“…2,3 Physiological forms of VP in the pediatric age group have been presumed to be a rare phenomenon. 4,5 As far as the authors could identify, articles in the English literature have been limited to normal variants of this condition. 5 However, condition may be more clinically important in children since because it can mimic inflammatory and infectious pathologies on magnetic resonance (MRI) and computed tomography (CT) imaging.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 As far as the authors could identify, articles in the English literature have been limited to normal variants of this condition. 5 However, condition may be more clinically important in children since because it can mimic inflammatory and infectious pathologies on magnetic resonance (MRI) and computed tomography (CT) imaging. 6 In 2016, Takata et al evaluated the relationship between sacroiliac pelvic morphology and VP in all age groups.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations